Marginalization of Indigenous People in Development: Antimun Bungkuak in the Heart of Minangkabau, Indonesia - Yazan, Sheiful; Arwemi, Arwemi; Kustati, Martin; Perrodin, David D; Elmizan, Gina Havieza (Yayasan Keluarga Guru Mandiri, 2025)
Indigenous communities are among the vulnerable groups at risk of being left behind in the development process. To uphold the